Strategies to optimize AED placements - Harika, Palla (Nanyang Technological University, 2019)
This Final Year Report analyses and reviews the current state of Automated External Defibrillators (AEDs) and their placement strategies in the Ang Mo Kio estate of Singapore. In the case of an out of hospital cardiac arrest (OHCA), time is of the utmost importance and for every minute that the arrest goes untreated, the chance of survival decreases by 10%. The addition of public-access AEDs is showing promising results in decreasing collapse-toshock times among OHCA patients and bystander access to these medical devices ensure that the necessary care to victims of OHCA is provided prior to arrival of emergency responders. Prior studies have implemented various methods such as mathematical optimization based on historical OHCA data and weighting of the different parameters like time, population density, against each other. These methods incorporate spatial covariates on OHCA occurrence, but do not provide precise distance coverage which are critical to the initial intent of such location analysis research. The purpose of this study is to provide a more holistic approach and method for generating placement strategies in the public estates of Singapore. This report aims to firstly visualize the differences in OHCA occurrences between the various years and study the effects on coverage by taking into account location hours-of-operation of the deployed devices. Next the novelty of this study is in (1) the use of route-based walking time instead of straight-line approximations, (2)the use of multiple strategies to balance decision-maker objectives; and (3) the implementation of an interactive decision-maker tool for observing effects on coverage. The approach is deployed and evaluated for a case study in the Ang Mo Kio Town, Singapore. The AED locations at the end of 2016 and OHCA data from 2011 up until 2016 was used in visualizations and risk analysis.